The CIA and the pursuit of security : history, documents and contexts - Dylan, Huw; Gioe, David, 1977-; Goodman, Michael S. (Intelligence, surveillance and secret warfare., 2020)
Written by intelligence scholars and experts, this book chronicles the evolution of the CIA: its remarkable successes, its controversial failures and its clandestine operations. The history of the agency is presented through the prism of its declassified documents, with each being supplemented by insightful contextual analysis.